PEMBUATAN MINUMAN PROBIOTIK SARI BUAH NANAS DENGAN VARIASI WAKTU FERMENTASI MENGGUNAKAN STARTER Lactobacillus fermentum InaCC B1295 - Putri, Yolanda Triana; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Pineapple is one type of fruit that is widely produced in Indonesia .This study to obtain the optimal fermentation time in the manufacture of pineapple juice probiotic drinks that meet quality standards and are favour by the panelist. The research was conducted experimentally using a completely randomized design (CRD) with four treatments and four replications in order to obtain 16 experimental units. The treatments used in this study were N1 (fermentation time of 8 hours), N2 (fermentation time of 12 hours), N3 (fermentation time of 16 hours), and N4 (fermentation time of 20 hours). The parameters observed were the degree of acidity (pH), total lactic acid, total lactic acid bacteria, total solids, and sensory assessment. The best treatment of pineapple juice probiotic drink fermentation time was N2 treatment (12 hours of fermentation time). The probiotic drink of pineapple juice had pH value of 4.03, total lactic acid 0.55%, total LAB 9.09 log CFU/ml, total solid 18.70%, slightly yellow color (3, 53), slightly pineapple aroma (3.80), slightly sour taste (3.87), and thin (2.60) viscosity..Keywords:Probiotic drink, fermentation time, Lactobacillus fermentum InaCC B1295Â